(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Diabetic polyneuropathy is the earliest and most common complication of diabetes mellitus. Diabetic polyneuropathy can develop in the early stages of carbohydrate metabolism disorder, moreover, distal polyneuropathy can also develop in patients with metabolic syndrome who do not have carbohydrate metabolism disorders. Hyperglycemia is the most important, but not the only risk factor for the development and progression of diabetic polyneuropathy. Peripheral nervous system damage in prediabetes and in the initial stages of diabetes mellitus mainly affects thin nerve fibers, which causes a fairly frequent development of disorders of the autonomic nervous system. Early diagnosis of diabetic polyneuropathy is extremely important, since lifestyle changes and increased physical activity can slow down the development of this complication. The ratio of oxidative stress severity and antioxidant defense activity is considered as a potential mechanism for early damage to the peripheral nervous system in hyperglycemia and as a possible target for therapeutic intervention. The review discusses the epidemiology, diagnostics, and potential therapeutic strategies for early diabetic polyneuropathy.